Concentrating and labeling genomic DNA in a nanofluidic array. Issue 3 (4th January 2018) - Marie, Rodolphe; Pedersen, Jonas N.; Mir, Kalim U.; Bilenberg, Brian; Kristensen, Anders
Abstract : Genomic DNA is concentrated in a dense nanofluidic array and labeled by a polymerase ϕ 29 reaction where neither the DNA nor the enzyme is attached to a solid support. Abstract : Nucleotide incorporation by DNA polymerase forms the basis of DNA sequencing-by-synthesis. In current platforms, either the single-stranded DNA or the enzyme is immobilized on a solid surface to locate the incorporation of individual nucleotides in space and/or time. Solid-phase reactions may, however, hinder the polymerase activity. We demonstrate a device and a protocol for the enzymatic labeling of genomic DNA arranged in a dense array of single molecules without attaching the enzyme or the DNA to a surface. DNA molecules accumulate in a dense array of pits embedded within a nanoslit due to entropic trapping. We then perform ϕ 29 polymerase extension from single-strand nicks created on the trapped molecules to incorporate fluorescent nucleotides into the DNA. The array of entropic traps can be loaded with λ-DNA molecules to more than 90% of capacity at a flow rate of 10 pL min −1 . The final concentration can reach up to 100 μg mL −1, and the DNA is eluted from the array by increasing the flow rate. The device may be an important preparative module for carrying out enzymatic processing on DNA extracted from single-cells in a microfluidic chip.